(untitled) (World Economics and Finance Bulletin, 2023)
With the rapid development witnessed in current days in variety of aspects, the innovation element is one of the important elements that economic units must take into consideration, due to its future effect on the economic unit’s position in the market. This research aims to study the use of the innovative green value chain in rationalizing costs, the research used a questioner form distributed to General Company for Textile and Leather Industries as the research sample. The targeted sample of respondents have the required knowledge and involvement in the main activities effected by the usage and application of green value chain in an economic unit. The results indicate that the usage of innovative green value chain not only reduces pollutant emissions, but can also as in costs rationalization